An assessment of diet among high-rank professional judo athletes - Ksiazek, A.; Kopeca, A.; Slowinska-Lisowska, M. (Journal of Combat Sports and Martial Arts, 2014)
Background. Rational diet is a major factor affecting the training process and sport success. The aim of the study was toHassess the energy value and the intakes of nutrients, minerals, vitamins, dietary fibre and water in daily food rations including and excluding supplements among high-rank male judo athletes. Material and methods. A total of 28 elite judoists (13 classified as first sport class, 12 as champions class, and 3 as international champions class) were included in the study. They engaged in sport professionally for an average 12.9 ± 3.7 years. The energy value of the diet and the amounts of the dietary ingredients were assessed on the basis of food diaries using the software Dieta 5.0. Results. The study has shown that the mean consumption of all the analysed dietary ingredients was significantly higher after taking into account food supplements and foodstuffs intended for special nutritional purposes. We found that supplementation with products containing proteins among professional judo athletes is not recommended. On the other hand, we found that supplementation of folic acid, vitamin D and calcium is justified. Of note is the fact that the recommended daily intakes of sodium, phosphorus, vitamin A and B - group vitamins (except for B2) were exceeded both in the diet without supplementation and in the diet with supplementation. Conclusions. The study casts doubt on the justifiability of using protein supplements. However, it seems justified to administer vitamin and mineral supplements, particularly those that contain vitamin D, folic acid and calcium.